1970
DOI: 10.3329/medtoday.v22i1.5601
|View full text |Cite
|
Sign up to set email alerts
|

Port Site and Intraperitoneal Infiltration of Local Anesthetics in Reduction of Postoperative Pain after Laparoscopic Cholecystectomy

Abstract: Laparoscopic cholecystectomy is now the gold standard technique for the treatment of gallstones disease. Although pain after laparoscopic cholecystectomy is less intense than after open cholecystectomy, some patients still experience considerable discomfort during the first 24 to 72 postoperative hours. The aim of this study is to evaluate the effect of intraperitoneal and port site instillation of local anaesthetics on pain relief in early postoperative period following laparoscopic cholecystectomy. Fifty pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 0 publications
3
27
0
3
Order By: Relevance
“…21 Alam et al who studied on port site and intraperitoneal infiltration of local anaesthetics in reduction of postoperative pain after laparoscopic cholecystectomy, showed port site, intraperitoneal infiltration of local anaesthetics for postoperative pain relief is, in this context, an effective alternative method for early pain control and minimize the need of analgesics. 22 Rt Shoulder-tip pain, which was slight during the first postoperative hours, tended to become predominant after 24 hr, while parietal pain and visceral pain rapidly decreased. Subdiaphragmatic administration of 80ml bupivacaine 0.125% plus epinephrine l/200,000 had no significant effect on total pain, parietal pain, visceral pain, or shoulder-tip pain as compared with saline.…”
Section: Post-operative Painmentioning
confidence: 99%
“…21 Alam et al who studied on port site and intraperitoneal infiltration of local anaesthetics in reduction of postoperative pain after laparoscopic cholecystectomy, showed port site, intraperitoneal infiltration of local anaesthetics for postoperative pain relief is, in this context, an effective alternative method for early pain control and minimize the need of analgesics. 22 Rt Shoulder-tip pain, which was slight during the first postoperative hours, tended to become predominant after 24 hr, while parietal pain and visceral pain rapidly decreased. Subdiaphragmatic administration of 80ml bupivacaine 0.125% plus epinephrine l/200,000 had no significant effect on total pain, parietal pain, visceral pain, or shoulder-tip pain as compared with saline.…”
Section: Post-operative Painmentioning
confidence: 99%
“…Shoulder pain mostly becomes apparent on the day after surgery when the visceral pain component has decreased. There are also great individual differences in pain perception after abdominal surgery [7].…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical trials have shown variable analgesic effects with a variety of methods including periportal infiltration of local anesthetics, intraperitoneal spraying above the gallbladder, and instillation into the subdiaphragmatic and subhepatic space covering the area of the hepatoduodenal ligament [7]. Bupivacaine administered in the subdiaphragmatic area is presumed to block noniceptive input generated from the inflamed diaphragmatic peritoneum [9].…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo un metaanálisis [20] donde fue válido la aplicación intraperitoneal de anestésico local. Dos en un estudio prospectivo, aleatorio doble ciego se encuentra efectividad en el uso de la bupivacaína para el control del dolor [21] estudian la bupivacaína empapada en una lámina de celulosa además de la infiltración en las incisiones de los trocares donde el resultado es la disminución del dolor postoperatorio [22] encuentran diferencia estadística en…”
Section: Análisis Estadísticounclassified